Enhancing titres of therapeutic viral vectors using the transgene repression in vector production (TRiP) system - H. E. Maunder (Nature Portfolio, 2017)
The maximum titre of therapeutic viral vectors can be adversely affected by the encoded transgene. Here the authors repress transgene expression in producing cells by employing the tryptophan RNA-binding attenuation protein and show that it improves titre of RNA- and DNA-based viral vectors expressing toxic transgenes.